EFEKTIVITAS PROGRAM KELAS BENSI ( KELUARGA SEHAT BEBAS HIPERTENSI) TERHADAP MANAJEMEN HIPERTENSI - Sri Wahyuni Adriani; Yulanda irma Tiara; Rias Elia Rahmad; Linda Putri Mahardika; Nur Fikriyah; Muhammad Imadduddin A (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
Background: Hypertension is a degenerative disease that is a major problem in the community. This disease is often called the silent killer because it has no symptoms. This study aims to analyze the effectiveness of the “Bensi Class” program on efforts to improve hypertension management in the Gumukmas, Puger and Lumajang areas. This intervention is different from other studies, other studies use lecture and booklet methods while